2023
DOI: 10.3389/fvets.2023.1276754
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the efficacy of humic acids to counteract the toxic effects of aflatoxin B1 in turkey poults

Jesús Adonai Maguey-González,
María de Jesús Nava-Ramírez,
Sergio Gómez-Rosales
et al.

Abstract: This study aims to evaluate the efficacy of humic acid (HA) from worm compost as an adsorbent for aflatoxin B1 (AFB1) in turkey poults. The experiment involved the inclusion of 0.25% (w/w) HA in the diet of turkey poults consuming aflatoxin-contaminated feed (250 ng AFB1/g). A total of 350 1-day-old female Nicholas-700 turkey poults were randomly allocated to five equal groups: negative control (basal diet); positive control (basal diet + 250 ng AFB1/g; HA (basal diet + 0.25% HA); HA + AFB1 (basal diet + HA + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…The observed benefits of HA on intestinal microbiota, gut integrity, ileal morphometry, and cellular immunity significantly strengthen the argument for their use as a practical and effective intervention against AFB 1 toxicity. These positive effects align with previous publications [ 12 , 13 ]. The improved villus height and width, indicative of enhanced nutrient absorption, corroborate the findings from Taklimi et al and López-García et al [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed benefits of HA on intestinal microbiota, gut integrity, ileal morphometry, and cellular immunity significantly strengthen the argument for their use as a practical and effective intervention against AFB 1 toxicity. These positive effects align with previous publications [ 12 , 13 ]. The improved villus height and width, indicative of enhanced nutrient absorption, corroborate the findings from Taklimi et al and López-García et al [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recent in vitro and in vivo studies have established the efficacy of humic acids (HA) in mitigating the detrimental effects of AFB 1 in turkey poults. These benefits include an improved performance and a significant reduction in aflatoxicosis severity [ 12 , 13 ]. Given the promising findings regarding the benefits of HA in mitigating AFB 1 toxicity in poultry, the present study aimed to assess the impact of dietary HA supplementation on various aspects of turkey poult health (intestinal microbiota, gut integrity, ileum morphometry, and cellular immunity) when fed an AFB 1 -contaminated diet.…”
Section: Introductionmentioning
confidence: 99%
“…This stock was subsequently used to contaminate the rest of the commercial feed, using 10 g of the stock per kg of feed. The composition of the diet was similar to previously reported data for turkeys (Maguey-González et al 2023 ). Batches of 30 kg were artificially contaminated to give a final content of 250 ng AFB 1 /g feed.…”
Section: Methodssupporting
confidence: 86%
“…Regarding the bursa/spleen ratio, there were no statistically significant differences between treatments. Maguey-González et al ( 2023 ) reported that the relative weight of the spleen and the bursa of Fabricius increased significantly in poults that were fed with a diet containing AFB 1 (250 ng AFB 1 /g feed). These results are in accordance with those obtained in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation